Measurement of the production cross section for Z plus b jets in proton-proton collisions at root s=13 TeV - CMS Collaboration; Damarseçkin, Serdal (AMER PHYSICAL SOC, 2022)
The measurement of the cross section for the production of a Z boson, decaying to dielectrons or dimuons, in association with at least one bottom quark jet is performed with proton-proton collision data at ffiffi s p ¼ 13 TeV. The data sample corresponds to an integrated luminosity of 137 fb−1, collected by the CMS experiment at the LHC during 2016–2018. The integrated cross sections for Zþ ≥ 1 b jet and Zþ ≥ 2 b jets are reported for the electron, muon, and combined channels. The fiducial cross sections in the combined channel are 6.52 0.04ðstatÞ 0.40ðsystÞ 0.14ðtheoÞ pb for Zþ ≥ 1 b jet and 0.65 0.03ðstatÞ 0.07ðsystÞ 0.02ðtheoÞ pb for Zþ ≥ 2 b jets. The differential cross section distributions are measured as functions of various kinematic observables that are useful for precision tests of perturbative quantum chromodynamics predictions. The ratios of integrated and differential cross sections for Zþ ≥ 2b jets and Zþ ≥ 1 b jet processes are also determined. The value of the integrated cross section ratio measured in the combined channel is 0.100 0.005ðstatÞ 0.007ðsystÞ 0.003ðtheoÞ. All measurements are compared with predictions from various event generators.
Keywords: PAIR PRODUCTION